Implementation of Character Development and Creativity Learning In the Thematic Learning Process of Elementary School - Amrina Izzatika; Muhammad Nurwahidin; Loliyana Loliyana; Dayu Rika Perdana; Ardhi Yudisthira (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Good character needs to be familiarized and exemplified in everyday life by teachers and parents. One character is instilled and accustomed to during that semester. Thus, 12 characters such as orderliness, patience, honesty, responsibility, forgiving, humble, care, sensitivity, concern, tolerance, self-control and wisdom have been formed in children during the 6 years of elementary school. Thematic learning is an interesting learning strategy a number of subjects that provide valuable experience educating students with concise language thematic learning is mixed learning a number of subjects or field studies in one theme. This integration can be seen from the aspects of process or time, curriculum, and teaching and learning aspects. Learning through character formation is the process of carving or sculpting the soul in such a way that it is 'formed' as unique, interesting, and different or distinguishable from others. Creativity learning is a term used in learning activities that have a relationship between creativity and student self-actualization which will be developed through thematic learning activities at school.